Experimental Research on 2 : 1 Parametric Vibration of Stay Cable Model under Support Excitation. (30th October 2016) - Zhang, Li-Na; Li, Feng-Chen; Yu, Xiang; Cui, Peng-Fei; Wang, Xiao-Yong
Abstract : For 2 : 1 parametric vibration problem of stay cable under support excitation, a sliding support only in the vertical moving is designed to simulate the bridge stay cable's vibration test model. Meanwhile, using numerical simulation of cable free vibration and dynamic characteristic test analysis, the experimental research under various conditions is implemented in the actual cable-stayed bridge as the research object, which is compared with the corresponding numerical simulation results. According to the analysis results, it shows that as the vibration test model has 2 : 1 parametric vibration under the support excitation the results of maximum cable displacement from experimental analysis and numerical simulation are basically consistent which revealed that the parametric vibration of stay cable exists and is easy to occur. Additionally, when the bridge bearing excitation frequency is similar to the 2 : 1 frequency ratio, small excitation can indeed lead to the sharp "beat" vibration of cable; therefore it is very necessary to limit the amplitude of support excitation to prevent the occurrence of a large main parametric resonance.